2015
DOI: 10.18632/oncotarget.3014
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral myeloid-derived suppressor and T regulatory PD-1 positive cells predict response to neoadjuvant short-course radiotherapy in rectal cancer patients

Abstract: Short-course preoperative radiotherapy (SC-RT) followed by total mesorectal excision (TME) is one therapeutic option for locally advanced rectal cancer (LARC) patients. Since radio-induced DNA damage may affect tumor immunogenicity, Myeloid-derived suppressor cells (MDSCs) and T regulatory cells (Tregs) were evaluated in 13 patients undergoing SC-RT and TME for LARC. Peripheral Granulocytic-MDSCs (G-MDSC) [LIN−/HLA-DR−/CD11b+/CD14−/CD15+/CD33+], Monocytic (M-MDSC) [CD14+/HLA-DR−/lowCD11b+/CD33+] and Tregs [CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 44 publications
0
35
0
Order By: Relevance
“…Chemotherapeutics or radiotherapy is known to trigger immunogenic cell death (Apetoh et al ., ; Welsh et al ., ). Recent report indicated that radiotherapy could induce the increase in PD1 + Tregs (Napolitano et al ., ). In the present study, we found that TIM3 expression in HNSCC postradiotherapy and HNSCC post‐TPF chemotherapy was significantly higher than that in primary HNSCC, which indicates that TPF chemotherapy and radiotherapy induce the up‐regulation of TIM3.…”
Section: Discussionmentioning
confidence: 97%
“…Chemotherapeutics or radiotherapy is known to trigger immunogenic cell death (Apetoh et al ., ; Welsh et al ., ). Recent report indicated that radiotherapy could induce the increase in PD1 + Tregs (Napolitano et al ., ). In the present study, we found that TIM3 expression in HNSCC postradiotherapy and HNSCC post‐TPF chemotherapy was significantly higher than that in primary HNSCC, which indicates that TPF chemotherapy and radiotherapy induce the up‐regulation of TIM3.…”
Section: Discussionmentioning
confidence: 97%
“…14,20 CRT also induces systemic immune changes, including reductions in circulating Tregs and myeloid-derived suppressor cells. 21 This immunomodulation may account for the reported abscopal effects on distant metastases after RT to the primary tumor, potentially mediated by cross-priming of T cells following tumor cell death. 12,18,19 Our results are consistent with previous reports of association between changes in Tregs and treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of HLA-DR low/ neg CD14 + MDSCs detected in the circulation of patients with melanoma [21], HCC [9,22], rectal cancer [23] and prostate cancer [24] correlated with poor prognosis; furthermore, a reciprocal relationship between Tregs and MDSCs has been demonstrated in HCC and prostate cancer patients [9,24,25]. In contrast, an inverse correlation between the frequency of MDSCs and presence of functional antigen-specific T cells found in melanoma patients and breast cancer patients highlights the potent immunosuppressive role of MDSCs in cancer [11,21].…”
Section: Role Of Mdscs In Suppression Of Anti-tumor Immunitymentioning
confidence: 99%